ANALISIS KAPABILITAS DINAMIS DALAM REHABILITASI DAN REKONSTRUKSI PASCA BENCANA DI KOTA PALU - Muhammad Alfian; Muhammad Rapi (Journal of Contemporary Public Administration, 2025)
The natural disaster that struck Palu City in 2018 had a significant impact on both the lives of its residents and the city’s infrastructure. In response, various rehabilitation and reconstruction programs have been implemented by the government in collaboration with humanitarian organizations. However, the effectiveness of these recovery policies continues to face numerous challenges. This study aims to analyze the extent to which dynamic capabilities comprising sensing, seizing, and transforming have been applied in the management of rehabilitation and reconstruction efforts in Palu City. A qualitative case study approach is employed to explore in depth the practices, obstacles, and potential of post-disaster recovery policies. Data were collected through in-depth interviews, field observations, and document analysis, with thematic analysis serving as the primary method of data processing. The findings indicate that in the sensing phase, the identification of community needs remains suboptimal due to weak inter-agency coordination and the lack of real-time data. In the seizing phase, the allocation of resources and strategic partnerships has not functioned effectively, hindered by bureaucratic barriers and overlapping programs among stakeholders. Meanwhile, in the transforming phase, the development of adaptive and sustainable systems still faces structural challenges such as land disputes and low community participation. The study concludes that the implementation of dynamic capabilities in Palu City requires further strengthening to ensure a more responsive, efficient, and sustainable recovery process in the face of future disasters.